Interrelation of Coalescence Theory and Qur’anic Perspectives on Rain Phenomenon: A Linguistic and Scientific Analysis - Sujiat Zubaidi; Aqdi Rofiq Asnawi; Muhamad Anwar Aditya (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2023)
The study of the rain phenomenon continues to develop over time, leading to the emergence of coalescence theory, a theory and model that discusses the occurrence of precipitation. This study aimed to reveal the connection between the theory of coalescence and Qur’anic perspectives on rain through the literature research framework to strengthen that al Qur’an has mentioned clearly before this theory was discovered through Qur’anic language miracle (al-i‘jāz al-bayānī) and scientific miracle (al-i‘jāz al-‘ilmī) in rain verses. This research concludes that rain can occur when water vapour in the atmosphere condenses into water drops that are large enough to fall to the Earth’s surface, which is influenced by several factors, including air humidity, air temperature, air pressure, and the presence of freezing nuclei to help the formation of water droplets when all these factors are met then it is the right time for the rain to fall because of the fulfilment of coalescence between particles ideally following coalescence theory. The Qur’an has already signalled through language miracles and scientific miracles in surah al-Nūr verse 43 and al-Rūm verse 48 that there is a correlation between the words yuzjī, saḥāb, riyāḥ and cloud formation, while the words yu’allif, and kisaf correlate with the combination of cloud droplets, and the word rukām correlate with increasing the size of the raindrops.